Sosialisasi dan Edukasi Keuangan Keluarga untuk Warga Desa Kuta Kabupaten Sumba Timur - Renggo, Yuniarti Reny; Hudang, Adrianus Kabubu; Ramompas, Yuvensius; Vindya Donna Adindarena; Karolina Albina Rewa; R.L.K.R Nugrohowardhani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Effective household financial management is a crucial pillar for the economic well-being of every family, particularly in the face of an uncertain economy and the challenges of modern life. Women hold a strategic position in improving household management because they have a greater ability to carry out household activities compared to men. The purpose of this activity is to highlight the role of women in enhancing household financial management, thereby supporting the sustainability of their families. This community service method employs a qualitative descriptive approach, utilizing data collection techniques that include initial surveys or observations, questionnaires, Focus Group Discussions (FGDs), and documentation in the form of photos, videos, and notes taken during the activity. The findings of this community service indicate that two activities are carried out: interactive lectures on family financial management and training on managing family finances. The results showed that 11 out of 13 participants had an understanding of family financial management education for Kuta village residents. In contrast, two people did not have a clear understanding of the training and lectures provided. These results indicate that not all RT mothers in Kuta village have the same sense of family financial management. Therefore, in the future, socialization and training in family finances are needed, involving more RT mothers in Desa Kuta.